Analisa Kapasitas Saluran Drainase Pada Jalan Raya Kelet - Bangsri - khoirul mahfidh, muhammad; Roehman, Fatchur; Wibowo, Kartono (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2022)
Drainage Jalan Raya Kelet - Bangsri, which is located in Jinggotan Village, Kembang District, Jepara Regency, is classified as an artificial drainage with a length of 725 meters. According to Muria News, “Jepara, 4/02/2020, it rained heavily from 10.30 to 15.00 on Jalan Raya Kembang - Bangsri, at that time there was a big flood which inundated the road as high as 30- 40 cm. Stagnant water occurs from the Flower Park to the Jinggotan bridge which is located to the south of SMA 1 Kembang. The flood disrupts the flow of local traffic, thereby inhibiting the speed of vehicles passing through it.